Catalogue of the types of the Scarabaeidae in the National Museum of Natural History of Luxembourg (Coleoptera) - Vitali, Francesco (ZooKeys, 2019)
The types of Scarabaeidae deposited in the collection of the National Museum of Natural History of Luxembourg are reported for the first time along with some historic and taxonomic remarks: Entypophanabiapicata Moser, 1913; Metabolusthibetanus Moser, 1914 (currently, Pseudosymmachia ); Autosericaannamensis Moser, 1915 (currently, Maladera ); Euphoresiaalboparsa Moser, 1913; Hybocamentaferranti Moser, 1917; Microsericaflaveola Moser, 1911; Triodontalujai Moser, 1917 (currently, Triodontella ); Trochalusferranti Moser, 1917; Anomalacondophora Ohaus, 1913 (currently, Mimela ); Amaurinaferranti Moser, 1911 (currently, Leucocelis ); Amaurinavittipennis Moser, 1909; Cetonia (Eucetonia) kolbei Curti, 1914; Lomapteradichropusviridipes Moser, 1908; Cosmovalgusferranti Moser, 1912.